Pengaruh Kualitas Pembelajaran Terhadap Kepuasan Mahasiswa - Puspasari, Dewi (Jurnal Etnik: Ekonomi-Teknik, 2021)
The research do to identified how description about quality learningwhich has been given by teacher to students, to identified howdescription about students satisfaction and to find out howsubstantial the influence of quality learning toward studentssatisfaction research on business management STIEB PerdanaMandiri Purwakarta 2017 are 86 students. The data sources used inthis research were primary and secondary data, data collectiontechnique used was using by questionnaire, data measurement usedwas Likert scale using validity and reliability and data analysistechnique used is simple linear regressions. The result of thesignificant test (t test) in this research was t count = 32.316 and asignificance of 0.000. the procedure for finding table statistics withcriteria for the level of significance (?=0.1) for the two-party testand df or dk (degrees of freedom) = total data - 2 or 88-2 = 86. Sowe get t_(table ) = 1,991 Thus, t_(count )?t_(table ) or 32.316 1.991and the probability value is 0.05 more than the Sig value (0.05 >0.000), then Ha is accepted and Ho is rejected, meaning that it issignificant and the value of R = 0.961 and the coefficient ofdetermination (Rsquare ) of 0.924 ( is the square of the correlationcoefficient or 0.961 x 0.961 = 0.924 ). This means that learningaffects the satisfaction of undergraduate students of the BusinessManagement Study Program while attending lectures 92.4%. Whilethe remaining 7.6% is determined by other factors.